Expression of STAT1 is positively correlated with PD-L1 in human ovarian cancer. Issue 10 (2nd October 2020) - Liu, Fangran; Liu, Jiao; Zhang, Jinguo; Shi, Jimin; Gui, Lu; Xu, Guoxiong
ABSTRACT: Signal transducer and activator of transcription 1 ( STAT1 ) is related to the immune microenvironment of tumorigenesis. The programmed cell death 1 (PD-1) and its ligand (PD-L1) have been reported to be important in immunotherapy by mediating tumor immune evasion. Blocking the PD-1/PD-L1 pathway can restore the endogenous anti-tumor immune response. This study aimed to examine the expression of STAT1, PD-1, and PD-L1 and the correlation between selected markers in human epithelial ovarian cancer (EOC). The results showed that malignant tumors contained more STAT1, PD-1, and PD-L1 positive cells. The expression of STAT1 and PD-L1 was associated with age, whereas PD-1 and PD-L1 associated with histopathological type, in patients with ovarian tumors. Moreover, the expression of STAT1 was found to be associated with disease stages and the grade of serous carcinoma. STAT1 expression was higher in OC cells than normal ovarian surface epithelial cells and was positively correlated with PD-L1 expression. The knockdown of STAT1 decreased PD-L1 expression, whereas overexpression of STAT1 increased PD-L1 expression. Furthermore, the expression of STAT1, PD-1, and PD-L1 was lower in paclitaxel-resistant cells than sensitive cells. Finally, STAT1 affected the overall survival and progression-free survival of patients with EOC. These findings suggest that STAT1, PD-1, and PD-L1 are the tissue markers of EOC and imply the possibility that the high level of STAT1, PD-1, and PD-L1 may favor the checkpoint immunotherapy in patients with EOC, but may have a limit in paclitaxel-resistant patients because of the low expression of STAT1, PD-1, and PD-L1 in paclitaxel-resistant cells.